The negative psychological impact of COVID-19 pandemic on mothers of children with attention deficit hyperactivity disorder (ADHD): a cross-section study - Amira Mohamed Yousef; Mohammad Gamal Sehlo; Amany Elshabrawy Mohamed (Middle East Current Psychiatry, 2021)
Abstract Background ADHD is an important cause for psychiatric care as one of the most prominent neurodevelopmental conditions. Being an ADHD child’s parent is a daunting and sometimes stressful job that becomes more challenging during the COVID-19 pandemic and its negative consequences. This cross-sectional study was applied to 54 mothers of ADHD children and adolescents; the data of the ADHD children and adolescents have been registered before the lockdown on their regular follow-up visits on the child and adolescent’s clinic of the psychiatry department. Data of the study were collected through an electronic Google form included a COVID-19 questionnaire, The Depression, Anxiety, and Stress Scale—21 Items (DASS-21) (Arabic version), and Conners’ Parent Rating Scale Revised-short version (CPRS-48). We aimed to assess symptoms of anxiety, depression, and stress symptoms among the mothers of ADHD children and adolescents during COVID-19 outbreaks and determine the relationship between these symptoms and the changed circumstances that occurred by the COVID-19 pandemic, also with the behavioral problem of their children that may deteriorate by their mothers’ psychological state. Results Most of our participants were from the low socioeconomic class and were married. In total, 29.6% of the mother of ADHD children had confirmed COVID-19 cases among their family members, while 11.1% of our subjects lost a family member due to this epidemic, 22% of our sample lost their work because of COVID-19. We found that the COVID-19 pandemic has a big financial drawback on the family of our participants by a percentage of 31.5%. We noticed that 48.1% of our sample documented domestic violence toward them compared to before COVID-19. A total of 92.6% of the mothers who participated in our study assessed the period of change and restrictions as being very demanding. We found that 74.1% of ADHD patients were not compliant with their medications than before the epidemic. Also, we found that the mothers of ADHD children have bigger challenges in managing the child’s meals, structured activities, and sleep compared to before COVID-19. We showed that 53.7% of the mothers had depressive symptoms, 61% had anxiety symptoms, and 53.7% had stress symptoms. These symptoms were statistically associated with the lost family member due to COVID-19, the financial drawbacks of the COVID-19 outbreak, and the domestic violence toward mothers, compared to before COVID-19, the non-compliance of their children on the medications compared to before COVID-19, the presence of confirmed COVID-19 cases among family members, mother’s assessment of the period of change and restrictions as being very demanding compared to before COVID-19, and the non-compliance of their children on the medications compared to before COVID-19 as well as the increased behavioral symptoms of their children. Conclusion COVID-19 pandemic has psychological influences on mothers of children with ADHD. A significant number of them may have depression, anxiety, and stress symptoms that could affect their children’s compliance with the medication and, consequently, their symptomatology.